Pendekatan Critical Regionalism pada Wisata Edukasi Tambak Garam di Amed, Karangasem: Bahasa Indonesia - I Komang Gelda Manika Aprizio; I Nyoman Gede Maha Putra; I Gusti Agung Putu Eryani (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
The decrease in the area of salt pond farming land in the Province of Bali as a result of greater use of coastal land as a support for the tourism sector resulted in a drop in the amount of salt produced in the Province of Bali. This issue has had an influence, resulting in the emergence of other issues such as decreased use of traditional food technology, decreased incomes and farming professions, and inadequate measures to maintain cultural assets associated with the ancient salt production method. Salt Pond Edutourism began as a reaction to existing challenges through its functions such as production and development, educational functions, and distribution. The exact location was chosen as Amed Hamlet, Purwakerti Village, Kec. Abang, Karangasem Regency since the area has a Geographical Indication certificate showing that salt goods originate from Amed with different salt properties than other salts. Following the stages of literature study, precedent study, observation by obtaining information from books, journals, newspapers, online media searches, and surveying. So that the results are obtained in the form of room and user specifications, as well as activities to be carried out in this area by implementing the concept of The Sustainability of Community Empowerment and applying the Critical Regionalism theme, which helps the surrounding area to have a strong identity, which is expected to influence the position of products in the market to improve the economy local community.